Ethanolic mangifera indica leaves extract as green corrosion inhibitor - Thivagaran, Rihashni; Nurjannah, Salim; Nurul Huda, Abu Bakar (Penerbit Akademia Baru, 2023)
Mangifera indica (MI) or mango leaf as a green corrosion inhibitor for copper has been studied. The MI was extracted in ethanol solvent and prepared at different concentrations of 0, 0.4, 0.6 and 0.8 mg/ml in 1 M HCl solutions to imitate the corrosive environment. The as-prepared MI extract analyzed by UV-Vis Spectrophotometer shows a shoulder peak at about 370 nm, resulting from the π → π* and n → π* electronic transition of aromatic C=C and carbonyl (C=O) functional groups. A Fourier transform infrared spectroscopy (FTIR) found that the MI extract exhibits aromatic C=C, C=O groups of phenolic compounds, C-OH, and C-O stretching vibrations. The electrochemical impedance spectroscopy (EIS) and Tafel plot analysis evaluate that the optimum corrosion inhibition of copper was achieved at 0.6 mg/ml concentration. The result is supported by a positive shift in the corrosion potential, Ecorr, lower corrosion current, Icorr and corrosion rate (CR) at-0.233 V, 4.39 µA/cm2 and 0.05 mm/yr, respectively. The surface morphology of the copper substrate after the corrosion test evaluated using metallurgical microscopy shows tremendous corrosion inhibition due to the adsorption of the molecules from the MI extracts.